The Importance of Intersectionality in Higher Education and Educational Leadership Research - Victoria Showunmi (Ali Khorsandi Taskoh, 2020)
This paper contributes to the literature on leadership and identity by examining how gender, race, and class may confer disadvantage or bestow privilege in accessing leadership positions while in the role of leader. The paper focuses on the methodology used to explore experiences of Black Minority and Ethnic (BME) and White women leaders understanding of these experiences in public and private sector organisations in England. The research offers the use of the author's autobiographical account as a starting point to develop an intersectional approach to leadership methodology. In addition, it draws on feminist, intersectional and critical auto-biographical theory to analyse the findings. The paper will begin with an introduction to the literature, moving onto the research design and then discussion on the initial findings, highlighting the core themes emerging from the data. Findings showed that the BME women experienced notably more challenges and difficulties in their role as leaders, and that they saw their ethnicity as having a clear bearing on their identities, their perception of leadership, and their experience as leaders.